Prevalence of Depression Among Women of Reproductive Age in the United States. Issue 4 (April 2018) - Guo, Nan; Robakis, Thalia; Miller, Claire; Butwick, Alexander
Abstract : OBJECTIVE: To describe the prevalence, use of antidepressants, and predictors of major and minor depression among nonpregnant women of childbearing age. METHODS: Using data from the National Health and Nutrition Examination Surveys 2007–2014, we performed a cross-sectional study of 3, 705 nonpregnant women of childbearing age. The primary outcome is the prevalence of major depression, and secondary outcomes are the prevalence of minor depression, rates of antidepressant use, and predictors of major and minor depression. Major and minor depression were classified using the Patient Health Questionnaire 9. Univariate and multivariate associations between major depression and minor depression with potential predictors were estimated using multinomial logistic regression. RESULTS: The overall prevalences of major and minor depression were 4.8% (95% CI 4.0–5.7%) and 4.3% (95% CI 3.5–5.2%), respectively. The prevalences of antidepressant use among women with major depression and minor depression were 32.4% (95% CI 25.3–40.4%) and 20.0% (95% CI 12.9–29.7%), respectively. Factors most strongly associated with major depression were government insurance (adjusted relative risk [RR] ratio 2.49, 95% CI 1.56–3.96) and hypertension (adjusted RR 2.09, 95% CI 1.25–3.50); for minor depression, these were education less than high school (adjusted RR 4.34, 95% CI 2.09–9.01) or high school education (adjusted RR 2.92, 95% CI 1.35–6.31). CONCLUSION: Our analysis indicates that 1 in 20 nonpregnant women of childbearing age experience major depression. Antidepressants are used by one third of those with major depression and one fifth of those with minor depression. Abstract : Nearly 5% of American women of childbearing age have symptoms of major depression, with nearly one third of women with severe symptoms reporting antidepressant use.